Fundamentals of Video Production for Modern Marketing - Grofelnik, Igor (Interdisciplinary and Applied Konwledge for Green and Digital Logistics Processes, 2026)
In the digital age, video production has become a key component of marketing strategies. As an engaging media format, video allows for the effective communication of information quickly, enhances brand visibility, and drives conversion. Despite its advantages, creating quality video content requires careful planning, technical expertise, and an understanding of the target audience. This article explores the three crucial stages of video production: pre-production, production, and post-production, emphasising the importance of grasping these fundamentals for successful video production in contemporary marketing.